In-Feed vs. In-Water Chlortetracycline Administration on the Fecal Prevalence of Virulence Genes and Pathotypes of Escherichia coli Involved in Enteric Colibacillosis in Piglets - Ramya Kalam; Raghavendra G. Amachawadi; Xiaorong Shi; Jianfa Bai; Mina Abbasi; Mike D. Tokach; Tiruvoor G. Nagaraja (Microorganisms, 2025)
Colibacillosis in nursery pigs, caused by Escherichia coli (ETEC, EPEC, and STEC pathotypes), remains a major economic concern in the swine industry. This study evaluated the effects of in-feed or in-water chlortetracycline (CTC) administration on the fecal prevalence of virulence genes and pathotypes associated with colibacillosis. A total of 1296 weaned piglets (21 days old) were allocated to 48 pens (16 pens/treatment; 27 piglets/pen) and assigned randomly to no CTC, in-feed CTC, or in-water CTC groups. CTC was administered from days 0 to 14. Fecal samples from five piglets per pen on days 0, 14, and 28 were enriched, screened by 11-plex PCR, cultured for pathotypes, and tested for CTC susceptibility and tetracycline resistance genes. None of the 360 fecal samples or 3267 E. coli isolates were positive for bfpA or aggA. Prevalence of estB (96.9%) and astA (92.8%) was highest. ETEC was the dominant pathotype (41.2%), with astA (29%) and estB (21.9%) as predominant enterotoxin genes. CTC administration had no significant effect on fecal prevalence of virulence genes or pathotypes (p > 0.05). stx2 and STEC were detected only at day 28, all harboring stx2e. All pathotypes were CTC-resistant, with tetA as the predominant resistance gene.